Response to Professor Feldmeier: By Paul John Shore (American Journal of Islam and Society, 2018)
Professor Feldmeier’s thoughtful response provides a useful context forconsidering both Lomellini’s work and the undertakings of seventeenthcentury Jesuits more generally. Jesuits such as De Nobili and Ricci were exceptionaland deeply engaged with the cultures with which they dialogued.Far more Jesuits were like Lomellini and knew what they believed to be trueabout other faith traditions from informants or books. Since these Jesuitshelped shape European perceptions of Islam, we need to learn more abouthow they understood that faith, and their own faith as well.